STAT3 mutations in “gray-zone” cases of T-cell large granular lymphocytic leukemia associated with autoimmune rheumatic diseases - Gorodetskiy, Vadim; Sidorova, Yulia; Biderman, Bella; Kupryshina, Natalia; Ryzhikova, Natalya; Sudarikov, Andrey (Frontiers in Medicine, 2022)
A persistently increased T-cell large granular lymphocyte (T-LGL) count in the blood of more than 2 × 109/L for at least 6 months is necessary for a reliable diagnosis of T-LGL leukemia. In cases with LGL counts of approximately 0.5–2 × 109/L, a diagnosis of T-LGL leukemia can be made if clonal rearrangement of T-cell receptor (TCR) genes is present and if the patient shows typical manifestations of T-LGL leukemia, such as cytopenia, splenomegaly, or concomitant autoimmune disease. However, in cases with LGL counts of less than 0.5 × 109/L, the diagnosis of T-LGL leukemia is questionable (termed as “gray-zone” cases). Although mutations in signal transducer and activator of transcription 3 (STAT3) gene are the molecular hallmark of T-LGL leukemia, their diagnostic value in the “gray-zone” cases of T-LGL leukemia has not been evaluated – our study has been aimed to examine the prevalence of STAT3 mutations in these cases. Herein, we describe 25 patients with autoimmune rheumatic diseases, neutropenia, clonal rearrangement of TCR genes, and circulating LGL count of less than 0.5 × 109/L. Splenomegaly was observed in 19 (76%) patients. Mutations in the STAT3 were detected in 56% of patients using next-generation sequencing. Importantly, in 3 patients, no involvement of the blood and bone marrow by malignant LGLs was noted, but examination of splenic tissue revealed infiltration by clonal cytotoxic T-lymphocytes within the red pulp, with greater prominence in the cords. We suggest using the term “splenic variant of T-LGL leukemia” for such cases.